Changes in autophagy in rats after spinal cord injury and the effect of hyperbaric oxygen on autophagy. (8th April 2016) - Sun, Yongming; Liu, Dong; Su, Peng; Lin, Fanguo; Tang, Qifeng
Highlights: Autophagy is activated in rats after SCI and sustained over a period of time. HBO treatment enhances autophagy expression in rats after SCI and accelerates cell repair rate. Autophagy may represent one of the mechanisms of action of HBO in the treatment of SCI. Abstract: The purpose of this study was to explore the effects of Hyperbaric oxygen (HBO) on the autophagic changes after induction of spinal cord injury (SCI) in rats. A total of 75 rats were randomly divided into the sham-operated group, the spinal cord injury group, and the SCI + HBO group. We found that at 7 d and 14 d after surgery, the BBB scores were higher in the SCI + HBO group in comparison to the SCI group. The expression of Beclin-1 and LC3II was upregulated in the SCI and SCI + HBO groups after SCI. Fluorescently stained Beclin-1 and LC3II proteins were barely detectable in the sham group. In contrast, Beclin-l and LC3II expression was observed in neurons and glial cells from the SCI and SCI + HBO groups. Beclin-1 and LC3II expression appeared at 6 h after SCI. At each time point, Beclin-1 and LC3II expression was significantly higher in the SCI + HBO group compared to the SCI group. These results suggest that autophagy is activated in rats after SCI and sustained over a period of time. HBO treatment enhances autophagy expression in rats after SCI and accelerates cell repair rate, which may represent one of the mechanisms of action of HBO in the treatment of SCI.